On-farm conservation of neglected and underutilized species: status, trends and novel approaches to cope with climate change: Proceedings of an International Conference, Frankfurt, 14-16 June, 2011 - Padulosi, S.; Bergamini, N.; Lawrence, T.; Bioversity International (2012)
This publication is the result of the International Conference held in Frankfurt, Germany 14-16 June 2011 organized in the framework of an International UN Project funded by IFAD “Reinforcing the resilience of poor rural communities in the face of food insecurity, poverty and climate change through on-farm conservation of local agrobiodiversity”. Twenty seven scientists from 11 countries participated and contributed to this publication with their long-term experience and expertise in agricultural research for the conservation and use of agrobiodiversity and the adaptation to climate change in support of the rural poor around the world. The lessons learnt through this exercise will be tested by the countries involved in the IFAD project (India, Nepal and Bolivia) and the results will be used for the development of enabling policies in support of in situ/on farm conservation of traditional crops and varieties/Neglected and Underutilized Species (NUS) around the world.